The Problems encountered by students during Mathematics online learning viewed from Constructivism: a study of students' perspectives - Roslani (International Journal of Progressive Mathematics Education, 2022)
Constructivism learning theory is very relevant to be applied in Indonesia because it has advantages that can be used as an innovative learning method. However, the constructivism learning model is still rarely applied, especially in mathematics learning so that the learning objectives are not achieved properly. This research was conducted to obtain comprehensive information on how constructivism theory is used in online mathematics learning and the obstacles faced. This can be useful to find out good new adaptations in implementing online mathematics learning in the future. In addition, it can be useful as an evaluation material for the application of constructivism theory in online mathematics learning in the future. This research uses descriptive analysis method with literature study technique. The constructivism theory referred to in this study is a constructivist learning theory that has been explored in the application of online mathematics learning into four parts, namely: a learner-centered learning environment, a knowledge-centered learning environment, an assessment-centered learning environment, and an assessment-centered learning environment. community-centred learning.